Pariwisata Berbasis Masyarakat Sebagai Pelestari Tradisi di Desa Samiran - Prasta, Made (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2021)
The purpose of this paper is to describe the exist traditions in Samiran Village and to study how far the people participation of Samiran Village as tradition preservers. A qualitative approach is used in this paper and described descriptively. Conducting literature studies, in-depth interviews, and observations is used in this paper. Assisted by participatory theory to analyze ho far the community participation as tradition preservers. The results show that the people of Samiran Village still carry out the sadranan and baritan traditions. The purpose of this tradition is to honor the ancestors, give thanks for the harvest, ask for blessings and a sense of mutual help. Community participation in tradition activities in Samiran Village consists of 2 types, namely active and passive participation. Direct participation carried on the tradition Sadranan, whereas indirect participation carried on the tradition baritan. With the concept of a community-based tourism, traditional activities can become a cultural tourist attraction. This paper proposes the role of the community as a preserver of tradition so that it is maintained and preserved. This paper also recommends a study on the role of the community as a preserver of other traditions that have not been mentioned by the author.